Avaliação de dispersantes químicos e pré-tratamentos na determinação de argila de solos de mineralogias distintas - RODRIGUES, Cristiane (2008)
The knowledge about the physical properties of soil, including the levels of clay is of paramount importance to the environment and for agriculture. Soil apparently equal may have different behavior because of inherent characteristics, determined by the performance of different procedures for training and the nature of their material trainer. The objectives of this study were pre-check treatments and methods of dispersal or chemical dispersants, combined or not, more efficient for determination of clay of some classes of land, also assessing the texture of field determined by a group of ten Pedólogos experienced. We selected five mineralogical contrasting nature of soil, Oxisols, Argisols, Nitosol and Chernosoils. Thirteen different treatments were used: using chemicals as dispersants, hydroxides sodium hydroxide, lithium and hexametafosfato; pre - treatment with Ditionito for disposal of iron and crystal ammonium oxalate to amorphous iron and hydrogen peroxide for disposal of organic matter, such as action mechanics were tested using sand as abrasive, the use of ultrasound and shaker horizontal movement of ribbon. There are data that need different treatment for determination of clay, taking into consideration the nature mineralogical; The lithium hydroxide is not efficient to disperse soil eletropositivos and very efficient to disperse soil electronegative; The use of sand as abrasive and ultrasound increased levels of clay in all treatments. The method that most closely approximated the texture of the field was that traditional uses sodium hydroxide and dispersant